Green coffee extract as a natural antioxidant in chill stored Indian mackerel (Rastrelliger kanagurta) mince - Parvathy, U.; Sivaraman, G. K.; Murthy, L. N.; Visnuvinayagam, S.; Jeyakumari, A.; Ravishankar, C. N. (Indian Journal of Fisheries, 2018)
This study was carried out to evaluate the effect of green coffee extract as a natural antioxidant for retarding lipid oxidation and protein degradation in mackerel mince. Based on preliminary product acceptability study, mackerel mince with two different concentrations of the extract (1.0 and 1.5%) and a control with no added extracts were prepared. Butylated hydroxytoluene, BHT (200 ppm) was used for reference. The experimental lots were stored at 4Â°C and samples were collected at regular intervals for a period of 8 days and analysed for nutritional quality indices. Green coffee extract was found to be effective in retarding lipid oxidation, as indicated by low levels of thiobarbituric acid-reactive substance (TBARS), peroxide values and subsequent protein changes by salt soluble nitrogen (SSN) degradation and loss of sulphydryl group. A shelf life extension of two days was observed in green coffee extract incorporated mince, compared to control and BHT treated lots. Study suggested a concentration of 1% green coffee extract to be effective as natural antioxidant in oxidation sensitive systems like mackerel mince.